O risco biotecnológico na forma de observação do futuro jurídico - Alves, Paulo Roberto Ramos (Universidade do Vale do Rio do Sinos, 2009)
The contemporary society has her functionality constituted under a paradoxical and risky reality. In that context, they appear in the social debates discussions concerning the risks happened of the fast evolution of the biotechnological communication. The establishment of specialized communications is characteristic of the functionally differentiated society, therefore, concomitantly to the well-known developments of the biotechnology, that communicative ambit produces risks to the which the society will be undeniably submitted. That fact potentiates the challenges of Law, suddenly the juridical practice stays harnessed to dogmatic, patrimonialist and universalist observations, evidencing a complete incapacity of reaction front to the problem of the biotechnological risk. In this way, the question under which settles the research says respect exactly to the possibility of delimitation of skilled juridical criteria to the administration of the biotechnological risk, evidencing, with that, constructivists po
Keywords: construtivismo; responsabilidade civil; risco; teoria sistêmica; biotecnologia; constructivism; risk; system theory; botechnology; civil liability; Ciências Sociais Aplicadas